2012
DOI: 10.1111/j.1432-2277.2012.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Children as donors: a national study to assess procurement of organs and tissues in pediatric intensive care units

Abstract: Summary A shortage of size‐matched organs and tissues is the key factor limiting transplantation in children. Empirical data on procurement from pediatric donors is sparse. This study investigated donor identification, parental consent, and effectuation rates, as well as adherence to the national protocol. A national retrospective cohort study was conducted in all eight Dutch pediatric intensive care units. Records of deceased children were analyzed by an independent donation officer. Seventy‐four (11%) of 683… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 18 publications
0
35
0
1
Order By: Relevance
“…4 Inquiry into the pediatric donation process and the specific factors influencing parental donation decisions should therefore be considered a national imperative. 5,6 Research to date has suggested that a number of factors affect parental authorization, including knowledge of organ donation and favorable donation attitudes. [6][7][8][9][10] For example, exposure to organ donation information, such as adequate knowledge of brain death, significantly predicts a favorable donation decision.…”
mentioning
confidence: 99%
“…4 Inquiry into the pediatric donation process and the specific factors influencing parental donation decisions should therefore be considered a national imperative. 5,6 Research to date has suggested that a number of factors affect parental authorization, including knowledge of organ donation and favorable donation attitudes. [6][7][8][9][10] For example, exposure to organ donation information, such as adequate knowledge of brain death, significantly predicts a favorable donation decision.…”
mentioning
confidence: 99%
“…Recognition of the potentially suitable donor can be challenging. A Dutch study of eight PICU's demonstrated a variation in their abilities to identify suitable donors from 60 to 90% . Other conditions such as severe sepsis, metabolic conditions, genetic abnormalities, previous malignancy or congenital heart disease are likely to represent the majority of those considered unsuitable, although data to support this are lacking.…”
Section: Why Is Od Uncommon In Paediatrics?mentioning
confidence: 99%
“…Decision makers for both adults and children consent relatively equally and the depth and detail of the donation discussion is associated with higher consent rates . Consent rates in Europe, North America, the UK and Australia for both adults and children range from 42 to 69% . In Australia, the rate is similar for adult (52.8%) and paediatric (50%) patients…”
Section: Consentmentioning
confidence: 99%
See 1 more Smart Citation
“…z obawy przed jeszcze większym obciążeniem emocjonalnym rodziców będących już w żałobie. Okazuje się, że pediatrzy (również za granicą) często nie są świadomi możliwości zakwalifikowania zmarłego dziecka jako dawcy narządów, co dodatkowo zmniejsza liczbę pobrań w tej grupie wiekowej [12]. Niestety psychologiczny aspekt pobrań od zmarłych dzieci nie jest tematem powszechnie poruszanym w krajowych publikacjach.…”
Section: Pacjenci I Metodyunclassified